Innovation Process: A Review of Existing Models and Development of an Alternative Model - Suziyana, Mat Dahan; Nurhaizan, Mohd Zainudin; Lee, Chia Kuang; Mohd Yusof, Taib (2011)

(untitled)
The intense competition in today’s global business environment has forced the manufacturers to innovate products more often. However, innovation process is risky and manufacturers often aim to introduce new products with lower development costs, shorter lead time and better quality. Thus, an appropriate innovation model needs to be developed to ensure that the objectives can be met. Previous works on product innovation revealed that a number of innovation models with different concepts and compositions have been produced and validated. The studies showed that previous researches were having disagreement on not only the most effective model of innovation, but also the key elements that affect a business’s ability to produce a successful innovation. This paper presents a review of the work related to innovation process including: the need for systematic innovation process, current models of innovation process and key elements of successful innovation. This paper then highlights the developments of an alternative innovation model, which focuses on the application of functional build (FB) approach to manufacturing process as an essential control element of the final product specifications.